The digestion and dietary carbohydrate pathway contains 100% gene mutations enrichment among 117 patients with major depressive disorder - Zhang, Ni; Li, Jin; Dong, Zaiquan; Hu, Yongbo; Zhong, Zhihui; Gong, Qiyong; Kuang, Weihong (Frontiers in Psychiatry, 2024)
Major depressive disorder (MDD) is partially inheritable while its mechanism is still uncertain. This cross-sectional study focused on gene pathways as a whole rather than polymorphisms of single genes. Deep sequencing and gene enrichment analysis based on pathways in Reactome database were obtained to reveal gene mutations. A total of 117 patients with MDD and 78 healthy controls were enrolled. The Digestion and Dietary Carbohydrate pathway (Carbohydrate pathway) was determined to contain 100% mutations in patients with MDD and 0 mutation in matched healthy controls.Findings revealed in the current study enable a better understanding of gene pathways mutations status in MDD patients, indicating a possible genetic mechanism of MDD development and a potential diagnostic or therapeutic target.